(untitled) (Web of Teachers: Inderscience Research, 2024)
Nikolai Ilyin is a Russian poet whose work reflects deep philosophical reflections about life, man and nature. His poetry is full of motifs that permeate all his works, which creates a holistic picture of the poet’s worldview.